Peran Guru IPS dalam Menanamkan Sikap Toleransi pada Lingkungan Sekolah di SD Inpres Perumnas 1 Waena Kota Jayapura. - Mutaqin, Alim; Mawara, Ricky Engel; Kulyasin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to describe and analyze the role of Social Studies teachers in instilling tolerance attitudes within the school environment at SD Inpres Perumnas 1 Waena, Jayapura City. The research background is based on the socio-cultural diversity of students, which requires strengthening character education, particularly tolerance values, in the learning process. This study employed a qualitative approach with a descriptive narrative design. The research subjects included Social Studies teachers as the main informants, the school principal, and students as supporting informants. Data were collected through observation, in-depth interviews, and documentation, while data analysis applied an interactive model consisting of data reduction, data display, and conclusion drawing. The findings reveal that Social Studies teachers play a strategic role in fostering tolerance through value integration in lesson planning, the implementation of group discussion strategies, contextual teaching approaches, and exemplary behavior in daily interactions. Supporting factors such as an inclusive school culture and teachers’ professional commitment strengthened the internalization process of tolerance values, while limited instructional time and curriculum demands posed significant challenges. The study concludes that strengthening the systematic and structured role of Social Studies teachers is essential in creating a harmonious and multicultural school environment.